How LMX Differentiation Attenuates the Influence of Ethical Leadership on Workplace Deviance: The Mediating Role of Psychological Empowerment - Guo, Yirong; Chen, Limei; Song, Lynda Jiwen; Zheng, Xiaoming (Frontiers in Psychology, 2021)
The previous research has mostly proposed that ethical leadership contributed to less deviant behavior; however, recent studies found that this relationship might not always be significant. Therefore, a deeper and more nuanced investigation of how and when ethical leadership influences deviant behavior is highly warranted. In the present research, drawing on social learning theory as our overarching theoretical framework, we posited that high level of LMX differentiation will impede the effect of ethical leadership on employee deviant behavior, and thus, ethical leadership could reduce employees’ deviant behavior in teams with lower LMX differentiation rather than high LMX differentiation. Furthermore, we proposed that the interactive effect of ethical leadership and LMX differentiation on employee deviant behavior is mediated by employee psychological empowerment. More specifically, ethical leadership is more likely to enhance employee psychological empowerment in teams with low LMX differentiation than in teams with high LMX differentiation, and enhanced psychological empowerment contributed to less deviant behavior. Through a multi-source field study via 379 paired samples from the southwest of China, we found support for all of our hypotheses. The results’ contribution to research on organizational behavior, limitations in the study, and future directions for researchers are also discussed.